2014
DOI: 10.5032/jae.2014.02106
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Effects that the Order of Abstraction and Type of Reflection have on Content Knowledge When Teaching Experientially: An Exploratory Experiment

Abstract: The purpose of this experimental study was to determine the effects of order of abstraction and type of reflection on student knowledge acquisition. Students were assigned randomly to one of four treatment combinations in the completely randomized 2x2 design which included either abstraction prior to or directly after an experience, and either reflection-in-action or reflection-onaction. A Lab-Aids® inquiry-based kit, centered on the principles of biofuels, served as the content for the treatment. The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(48 citation statements)
references
References 22 publications
2
43
1
Order By: Relevance
“…Lamm, Rhoads, et al (2011) found that "those with a strong preference for abstract categorization (thinking) and active experimentation (doing) when learning had a very strong relationship with several critical thinking items" (p. 20). However, Baker et al (2014) found no statistically significant difference in student content knowledge regarding the timing of when an abstract conceptualization occurred in the experiential learning model.…”
Section: Theoretical Frameworkmentioning
confidence: 64%
See 3 more Smart Citations
“…Lamm, Rhoads, et al (2011) found that "those with a strong preference for abstract categorization (thinking) and active experimentation (doing) when learning had a very strong relationship with several critical thinking items" (p. 20). However, Baker et al (2014) found no statistically significant difference in student content knowledge regarding the timing of when an abstract conceptualization occurred in the experiential learning model.…”
Section: Theoretical Frameworkmentioning
confidence: 64%
“…Specifically, the four steps in the learning process are (a) concrete experience, (b) reflective observation, (c) abstract conceptualization, and (d) active experimentation (Kolb, 1984). For learning to occur, learners must be guided through the full cycle; however, where the cycle begins for each student should not be a concern for teachers ( Baker et al, 2014;Kolb, 1984). Lamm, Rhoads, et al (2011) found that "those with a strong preference for abstract categorization (thinking) and active experimentation (doing) when learning had a very strong relationship with several critical thinking items" (p. 20).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of sequencing an initial exposure to instructional information from a specific end of the ELT continuum has not been fully examined. Baker, Brown, Blackburn, and Robinson (2014) conducted an initial examination into presentation order of concepts within the context of experiential learning theory for post-secondary students using agriculture as the context. While their findings failed to reveal significant differences between order of abstraction and type of reflection, they recommended further research in this area, specifically within the secondary classroom.…”
Section: Review Of Literaturementioning
confidence: 99%